Iron plaque decreases cadmium accumulation in Oryza sativa L. and serves as a source of iron. (3rd September 2016) - Sebastian, A.; Prasad, M. N. V.
Abstract: Cadmium (Cd) contamination occurs in paddy soils; hence it is necessary to reduce Cd content of rice. Application and mode of action of ferrous sulphate in minimizing Cd in rice was monitored in the present study. Pot culture with Indian rice variety Swarna (MTU 7029) was maintained in Cd‐spiked soil containing ferrous sulphates, which is expected to reduce Cd accumulation in rice. Responses in rhizosphere pH, root surface, metal accumulation in plant and molecular physiological processes were monitored. Iron plaque was induced on root surfaces after FeSO4 application and the amount of Fe in plaque reduced with increases in Cd in the soil. Rhizosphere pH decreased during plaque formation and became more acidic due to secretion of organic acids from the roots under Cd treatment. Moreover, iron chelate reductase activity increased with Cd treatment, but in the absence of Cd, activity of this enzyme increased in plaque‐induced plants. Cd treatment caused expression of OsYSL18, whereas OsYSL15 was expressed only in roots without iron plaque. Fe content of plants increased during plaque formation, which protected plants from Cd‐induced Fe deficiency and metal toxicity. This was corroborated with increased biomass, chlorophyll content and quantum efficiency of photo‐synthesis among plaque‐induced plants. We conclude that ferrous sulphate‐induced iron plaque prevents Cd accumulation and Fe deficiency in rice. Iron released from plaque via organic acid mediated dissolution during Cd stress.